SYNTACTIC ALIGNMENT AND VARIATION IN KAZAKH INTONATION UNITS: A CROSS-GENRE AND BILINGUAL PERSPECTIVE - Shaibek, Zhansulu (Nazarbayev University School of Sciences and Humanities, 2025)
This project is motivated by a desire to investigate the linguistic organization of spoken Kazakh, particularly in the shape and types of intonation units in real-time discourse. Building on existing work in Japanese (Matsumoto 2003), Spanish and Khanty (Sosa 2020), and Hebrew (Izre’el 2005), this study positions Kazakh within the broader typology across languages. It aims to enrich our understanding of the human linguistic faculty by examining how Kazakh speakers—only using Kazakh, Russian or code-switching—navigate the demands of spontaneous and semi-planned speech.
Keywords: prosody; intonation units; syntactic alignment and variation; bilingualism; type of access: embargo